Pelatihan ToT Peningkatan Literasi Teknologi pada Guru di Pondok Pesantren Ibadurrahman Temas: Dampak pada Efektivitas Pembelajaran - Suhaedi, Wirawan; Waskito, Iman; Rakhmawati, Intan (Jurnal Gema Ngabdi, 2024)
In the digital era, information technology has become an important component in various aspects of life, including education in Islamic boarding schools. Islamic boarding schools are educational institutions that not only focus on religious education, but also academics with technological literacy. Therefore, increasing technological literacy for teachers in Islamic boarding schools through structured training is very necessary to support the effectiveness of learning. The training method is Training of Trainers (ToT). Through this activity, teachers at Ibadurrahman Temas Islamic Boarding School showed a significant increase in technological literacy. This also encourages efficiency and effectiveness of learning, as well as a continuous training system that supports technological literacy in Islamic boarding schools